Synthesis and analysis of a new high intensity phthalocyanine pigment containing nitrogen, sulfur and copper - Robiddinova Mukhlisa; Yusupov Muzafar; Sherkuziev Doniyor (E3S Web of Conferences, 2024)
The article presents the results of research on obtaining highly intensive pigments based on organic and inorganic substances. The process of synthesis of copper chloride (CuCl) raw material with phthalic anhydride, inorganic and organic substances was studied. As a result of the study, copper chloride (CuCl) and a sample of the pigment obtained as a result of neutralization with sulfuric acid were analyzed using an X-ray spectrum. According to the results of the analysis, a new type of pigment based on copper phthalocyanine (CuPc) was selected as the most optimal option, and physico-chemical analysis of the sample (elemental analysis (SEM_EDX)) was studied. It has been determined that the highly intensive pigment obtained as a result can be used as an import substitute product in the construction and textile industry.